2014
DOI: 10.1186/s12863-014-0142-3
|View full text |Cite
|
Sign up to set email alerts
|

Normal adult survival but reduced Bemisia tabaci oviposition rate on tomato lines carrying an introgression from S. habrochaites

Abstract: BackgroundHost plant resistance has been proposed as one of the most promising approaches in whitefly management. Already in 1995 two quantitative trait loci (Tv-1 and Tv-2) originating from S. habrochaites CGN1.1561 were identified that reduced the oviposition rate of the greenhouse whitefly (Trialeurodes vaporariorum). After this first study, several others identified QTLs affecting whitefly biology as well. Generally, the QTLs affecting oviposition were highly correlated with a reduction in whitefly surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Despite the correlation between adult survival and oviposition rate, there was no overlap in associated SNPs between the two parameters. These data suggest that certain traits can affect oviposition rate without influencing adult survival, a phenomenon that has previously been shown for the silverleaf whitefly Bemisia tabaci on wild tomato plants [ 41 ]. It is conceivable that certain plant traits negatively affect the reproduction of whitefly adults but are not lethal to them.…”
Section: Discussionsupporting
confidence: 63%
“…Despite the correlation between adult survival and oviposition rate, there was no overlap in associated SNPs between the two parameters. These data suggest that certain traits can affect oviposition rate without influencing adult survival, a phenomenon that has previously been shown for the silverleaf whitefly Bemisia tabaci on wild tomato plants [ 41 ]. It is conceivable that certain plant traits negatively affect the reproduction of whitefly adults but are not lethal to them.…”
Section: Discussionsupporting
confidence: 63%
“…Two B. tabaci resistance‐related fatty acid constituents also mapped in this region (Figure ). Recently, using the same S. habrochaites population, a QTL on Chromosome 5 ( OR‐5 ) was identified that only reduced the OR of B. tabaci (Lucatti et al ). That QTL co‐localized with a minor hotspot metabolite QTL associated to resistance to B. tabaci in our F 2 population.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether the one currently identified QTL for F. occidentalis resistance applies to resistance to other thrips species, but our results suggest this is unlikely. In other plant-insect combinations, resistance mechanisms were also found to be highly insect species-specific, even on the level of the developmental stage of the insect (Hilder & Boulter, 1999;Lucatti et al, 2014;Soria & Mollema, 1995).…”
Section: Con Clus Ionsmentioning
confidence: 99%